Investigation of the relationship between the parameters of electric response to impact excitation of porous heterogeneous materials and variations in their strength under the conditions of cyclic freezing-defreezing; Russian journal of nondestructive testing; Vol. 46, № 1 - Fursa T. V. Tatyana Viktorovna (2010, 2010)
A decrease in the strength of cement-sand specimens due to cyclic alternating_sign tem_perature excitation is shown to yield a shift of the principal maximum and the entire spectrum of theelectric response to an impact excitation towards lower frequencies, spectrum broadening, and dete ioration of the spectral maxima quality factor